Wood in Civil Engineering 2017
DOI: 10.5772/67129
|View full text |Cite
|
Sign up to set email alerts
|

Grading of Low-Quality Wood for Use in Structural Elements

Abstract: Timber is a sustainable resource, environmentally friendly and aesthetically pleasing. Using locally grown timber as building material leads to economic, social and environmental benefits. Being an organic material, timber is not homogeneous; hence, it is crucial to predict the base material quality. International codes require the use of wood previously graded according to the current regulations in order to verify its reliability when used as structural material. An exhaustive analysis of the state of art of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The model was divided into three parts for clarity: twist, bow, and cup. Bow and cup were based upon classic mechanics of materials equations, while twist used Lekhnitskii 17 approach considering the orthotropic nature of the wood. Despite being treated individually, the forces computed for each out-of-plane defect will be summed up for a final estimation of a pressure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was divided into three parts for clarity: twist, bow, and cup. Bow and cup were based upon classic mechanics of materials equations, while twist used Lekhnitskii 17 approach considering the orthotropic nature of the wood. Despite being treated individually, the forces computed for each out-of-plane defect will be summed up for a final estimation of a pressure.…”
Section: Methodsmentioning
confidence: 99%
“…For the twist component of the model, the derived relationship from Lekhnitskii 17 was chosen, which is a particular case of the principle of Saint Venant for rectangular sections in orthotropic materials (see Figure 5 and equation ( 1)). All geometric parameters such as twist angle (θ) and twist length (L1, L2) can be taken from the laser measurement and the surface graph.…”
Section: Twist Modelmentioning
confidence: 99%
“…The benefits brought by the cross-layer configuration to the mechanical characteristics of the CLT also allow the use of wood species with poor mechanical properties. This has a positive impact in terms of sustainability, as it favors the use of local wood species that have mechanical characteristics lesser than those of Central Europe species traditionally used in the production of laminated timber [11,12]. CLT is very suitable for prefabrication, as it allows most elements to be produced in the factory and essentially only the connections to be left to construction site operations.…”
Section: Sustainability Of Timber As a Building Materialsmentioning
confidence: 99%
“…It is generally characterized by medium-low quality due to the presence of defects (knots, clusters of knots, resin pockets, grain deviation, etc.). Previous research about its yield for structural use showed that about 50% of the boards had to be rejected due to their defects [40][41][42], so that the possibility of defining the structural quality of the boards already in the wet state is a fundamental step to ensure the sustainability of the entire production process. In fact, the ability to provide a pre-grading on wet boards could significantly increase the profitability by saving the cost of drying and subsequent processing for non-structural grade boards sold at the same price whether wet or dry.…”
Section: Introductionmentioning
confidence: 99%